The Stability of Islamic Finance: Creating a Resilent Financial Environment for a Secure Future - Hossein Askari, Zamir Iqbal (Wiley Finance, 2010)
The new book by a group of four Western-trained Islamic economics is greatly welcomed. It builds on and extends their earlier work on the topic and will become essential reading for all those with an interest in the economic implications of Islamic finance. The stability of Islamic Finance develops themes that link Islamic finance to existing traditions in economics; that assess the stability properties of Islamic financial instruments, and that explain some of the key Islamic concepts in economists term. It will be an invaluable source for thse who want to know more about the nature of the financial instruments that go to make up an Islamic financial system, and to understand how an Islamic financial system might work in a twenty-first century context. It is a provocative and insightful assessment of the economic properties of Islamic finance that deserves to be read and reflected on by Islamic and non-Islamic economists alike.